Reactivity of a dihydroboron species: synthesis of a hydroborenium complex and an expedient entry into stable thioxo- and selenoxo-boranes1. Issue 36 (28th September 2015) - Jaiswal, Kuldeep; Prashanth, Billa; Ravi, Satyam; Shamasundar, K. R.; Singh, Sanjay
<x xml:space="preserve">Abstract</x> Oxidative insertion of sulfur or selenium into the B–H bonds, of bis(phosphinimino)amide stabilized dihydroboron species, followed by H2S or H2Se evolution leads to a facile access to stable thioxo- and selenoxo-boranes.